1995
DOI: 10.1111/j.1399-0039.1995.tb02427.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA in familial and nonfamilial Mediterranean Kaposi's sarcoma in Greece

Abstract: Fifty-four (54) unrelated patients with Mediterranean Kaposi's sarcoma (MKS) and 8 patients members of 4 unrelated families with familial MKS were serotyped for HLA-A,B and DR antigens. The diagnosis was histologically confirmed and all patients were negative for anti-HIV antibodies. An increased frequency of HLA-B18 (44.4% vs 14.2% in the controls, p < 0.001, RR = 4.8) and HLA-DR5 (57.6% vs 37.2% in the controls, p < 0.025, RR = 2.29) was observed in the group of patients with MKS. Seven (7) of the 8 family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…Indeed, previous studies showed an increase in frequency of HLA-DR5 in Kaposi's sarcoma patients, although this data remains controversial [Contu et al, 1984;Kaloterakis et al, 1995]. It would be of interest to analyze the potential correlation between HHV-8 infection and the prevalence of some genetic traits that have been described as frequent among the Sardinian population and relatively rare in most of the Caucasian population.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, previous studies showed an increase in frequency of HLA-DR5 in Kaposi's sarcoma patients, although this data remains controversial [Contu et al, 1984;Kaloterakis et al, 1995]. It would be of interest to analyze the potential correlation between HHV-8 infection and the prevalence of some genetic traits that have been described as frequent among the Sardinian population and relatively rare in most of the Caucasian population.…”
Section: Resultsmentioning
confidence: 96%
“…6,7 In North America, Classic Kaposi Sarcoma is rare with an incidence of 2.6-4.1/million men and 0.6-0.9/ million women 4 compared with incidences as high as 50/million men and 28/million women in rural areas of Italy 8 and 16.9/million men and 6.3/million women in Israel. 9 In addition to this classic variant Our series identifies Classic Kaposi Sarcoma in the United States as a disease predominantly of Caucasian Americans, followed by Mediterraneans, Hispanics, and Black Americans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, risk of developing HHV-8-associated Kaposi's sarcoma has been associated with HLA-DR5 in both 'classical' [43,44] forms of the disease as well as in HIV-associated Kaposi's sarcoma (along with HLA-DR1) [45][46][47][48][49][50][51] in Caucasian (but not African [52]) populations, whilst HLA-DR3 (a component of the HLA-B8-associated ancestral MHC haplotype) is protective [50,51]. In the case of the common Caucasian MHC haplotype that includes HLA-A1/ -B8/-DR3 alleles, these data indicate that individuals carrying this haplotype experience more rapid CD4 Tcell decline and are generally at increased risk of opportunistic infections; but at the same remain at low risk of developing Kaposi's sarcoma [50,51].…”
Section: Modulating Hiv Disease Progression At Multiple Levelsmentioning
confidence: 99%